Prevalence of Metabolic Syndrome in Hospitalized Female Psychiatric Patients: A Cross-Sectional/Single-Center Study in Iran (2021–2022) - Maryam, Mobini; Ali, Mohammadpour Reza; Aref, Hoseini; Forouzan, Elyasi (SN comprehensive clinical medicine, 2025)
Background Metabolic syndrome (MetS) is a global pandemic, making it a serious public health concern. Individuals with psychiatric disorders have a higher risk of developing MetS. Purpose This study aimed to assess MetS in people suffering from psychiatric disorders. Methods From 2021 to 2022, a cross-sectional study was conducted on inpatients at the general teaching hospital in Sari, Iran. The study included 100 women with psychiatric disorders. MetS was initially diagnosed based on the National Cholesterol Education Program/Adult Treatment Panel III (NCEP/ATP-III) guidelines and the International Diabetes Federation (IDF) criteria [1]. Data were analyzed with the SPSS software package (version 20). Results The study included 100 female patients with a mean age of 45.28 ± 12.76 years. The majority of them were married (70%). Twenty-one percent of participants had high-income jobs, with a mean BMI of 30.04 ± 6.00 kg/m 2 and a mean waist circumference of 88.07 ± 12.41 cm. Psychotropic medication use was reported by 98% of participants. According to the NCEP/ATP-III guidelines, MetS was observed in 55% of cases with psychiatric disorders. Patients with psychiatric disorders had high hypercholesterolemia. Conclusion Given the high prevalence of MetS, routine metabolic screening should be included in psychiatric care to reduce cardiovascular risk. MetS was diagnosed in approximately half of the patients suffering from psychiatric disorders. Because of the significance of this association, it is recommended that MetS be assessed in patients with these disorders. Because of this, understanding the parameters involved in MetS may help physicians and patients choose or modify their treatment options, lifestyles, and self-care programs.